2013
DOI: 10.1007/s00520-013-1981-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two chemotherapy-induced peripheral neuropathy measurement approaches in children

Abstract: Prospective measures of CIPN using the ped-mTNS identified a far greater proportion of subjects with peripheral neurotoxicity as compared to CTCAE v3.0 sensory and motor neuropathy ratings, and thus we recommend the use of a specific measure of CIPN such as the ped-mTNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 22 publications
3
63
0
Order By: Relevance
“…However, until date there is no universally accepted tool for diagnosing chemotherapyinduced peripheral neuropathy in children and several scales (including or not electrodiagnostic studies) have been used to detect this complication in children receiving chemotherapy (12,27,28). Some examples are: the total neuropathy scale (TNS), clinical neuropathy scale, and the modified neuropathy scale.…”
Section: Study Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, until date there is no universally accepted tool for diagnosing chemotherapyinduced peripheral neuropathy in children and several scales (including or not electrodiagnostic studies) have been used to detect this complication in children receiving chemotherapy (12,27,28). Some examples are: the total neuropathy scale (TNS), clinical neuropathy scale, and the modified neuropathy scale.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Some examples are: the total neuropathy scale (TNS), clinical neuropathy scale, and the modified neuropathy scale. Recently, the modified pediatric scale for total neuropathy (ped-mTNS) was validated as a variant of TNS (for not including electrodiagnostic studies), and has been considered as a reliable and valid measure for detecting CIPN in children with cancer and leukemia (27,28). Moreover, it has been also reported that sensitivity to detect CIPN with this scale is greater than with previous ones.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-seven full text articles were screened for full inclusion and exclusion criteria and 42 were excluded; 4 were not conducted with pediatric patients, 17 did not include patient-report, 12 were conference proceedings, and 6 were duplicate articles. A total of 5 full text articles met eligibility criteria and were included [6, 8, 1214]. Figure 1 demonstrates the flow for article identification and selection.…”
Section: Resultsmentioning
confidence: 99%
“…In many clinical studies, the Common Terminology Criteria for Adverse Events (CTCAE) are used to report toxicities, but they have been shown to under-report the incidence of CIPN by up to 40 % [68]. Comprehensive clinical neurological exams tend to be poorly reproducible, inconsistent, or incomplete in their assessment of CIPN [7].…”
Section: Introductionmentioning
confidence: 99%